The effect of the m-shape carrying method on sleep quality in infants aged 3-6 months - Septi Kurniawati; Febrina Dwi Rahmawati; Tria Eni Rafika Devi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Sleep is essential for a baby's growth and development. One way to promote better sleep is to use the M-shape carrying technique, an ergonomic position that mimics the baby's natural position in the womb. Purpose: To examine the role of ergonomic baby carrying in a baby carrier in determining how well babies aged 3–6 months sleep. Method: A pre-experimental study with a single-group design before and after treatment was conducted. A total of 45 babies aged 3 to 6 months were selected through purposive sampling. Data were collected using a questionnaire, and the results were analyzed using the Wilcoxon statistical test. Results: The study showed a significant difference in infant sleep quality before and after using the M-shape carrying method, with a p-value of 0.000 (p < 0.05), indicating a positive effect. The use of the M-shape carrying position has been shown to help improve sleep patterns and comfort levels in babies aged 3 to 6 months. Conclusion: This approach can be an effective non-drug method to support improved infant sleep quality